Administrative-Procedural Form and Stages as Elements of the Characteristics of the Administrative Process - Spiridonov, P. E. (Sibirskoe ûridičeskoe obozrenie (Online), 2021)
The subject of research in this paper is the administrative-procedural form and stages of the administrative process. The purpose of the study is to analyze the essential characteristics of the administrative-procedural form and stages. It is stated that the evolution of the administrative process and administrative-procedural legal relations entailed changes in the administrative-procedural form, which were influenced by changes in the political system and the system of public administration in the Russian Federation. It is concluded that the improvement of the administrative process and its form ensures compliance with both the interests of the state and society, as well as the rights and legitimate interests of citizens. Attention is drawn to the fact that one of the characteristic features of administrative-procedural legal relations that distinguish it from other types of procedural legal relations – arbitration, civil, criminal, constitutional, is the administrative-procedural form, which is characterized by out-of-court, pre-trial and judicial procedures of proceedings in an administrative case, due to the specifics and features of its subject. The author notes that the administrative-procedural form is an external expression of administrative-procedural activity, and the stages are its internal content. At the same time, the stages of the administrative process are separate, but interrelated stages consisting of administrative procedural actions united by common tasks and intermediate and final administrative procedural decisions, procedural deadlines. Attention is drawn to a certain specificity of the stages of the administrative process, which consists in the fact that they cannot be clearly divided into judicial and pre-trial stages, as it is in the criminal process. The system of stages of the administrative process should be the same for all types of administrative proceedings, since this follows from the principle of self-similarity, when the particular comes from the general and corresponds to it. To determine the place of administrative judicial procedure in the administrative process, it is necessary to understand that the court, as a subject of administrative procedural legal relations, can enter into the process at different stages, and it is not the only subject of administrative procedural relations that makes legally significant procedural decisions. The methodological basis of the article is dialectical, formal-logical methods, formal-legal method and method of interpretation of law.